MOBILE GAS ANALYZERS: PORTABLE SOLUTIONS AND THEIR APPLICATIONS IN INDUSTRIAL AND ENVIRONMENTAL MONITORING (European Journal of Economics, Finance and Business Development, 2024)
This article is dedicated to analyzing the significance of portable gas analyzers in industry and environmental monitoring, their technical characteristics, and areas of application. Gas analyzers play a crucial role in detecting hazards associated with harmful gases and pollutants, and their use aids in optimizing production processes, protecting the environment, and ensuring worker safety. The article thoroughly examines the technical aspects of device operation through core components such as sensor technologies, mobile communication systems, and software. It also describes testing methods that assess key device parameters such as reliability, response speed, and sensitivity to environmental factors. The experiments and analyses presented demonstrate ways to improve device efficiency, enhance sensor sensitivity, and reduce their susceptibility to external conditions. Recommendations for future research and developments open up opportunities to enhance the reliability of portable gas analyzers and expand their application areas. This scientific work not only highlights key technological achievements and scientific progress in the field of portable gas analyzers but also contributes to a deeper understanding of their role in industry and environmental monitoring, thereby encouraging their effective use in various sectors.